A bibliometric analysis of academic misconduct research in higher education: Current status and future research opportunities. (18th August 2021) - Ali, Imran; Sultan, Parves; Aboelmaged, Mohamed
ABSTRACT: The literature on academic misconduct has seen unprecedented growth over the past 20 years. As the research into this vital topic has grown, there have been a few reviews attempting to consolidate the literature. While the extant reviews have been insightful, a careful analysis reveals that these have somewhat different emphases, methods, and time intervals. Our study employs a bibliometric analysis approach on a large set of studies (779) published between 2000 and 2020. The analysis uncovers the key clusters, countries' co-authorship and evolution of research over the past two decades. It enriches contemporary knowledge on multifaceted issues of academic misconduct and offers resonant insights for academics, students, and policymakers. The paper concludes with several promising opportunities for future research.